(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Corporate financial reporting is an essential activity for all businesses. This form of accounting should provide investors and creditors with useful information that they can employ in making lending or investment decisions. Since stockholders and lending institutions rely on income or repayment from your business to accurately run their own companies and estimate their cash flow, it’s essential that your company be able to present accurate, timely information that speaks to the overall health of your company. Failure to provide accurate information can not only lead to problems of reputation it can cause legal difficulties. This paper reflects overview of corporate financial Reporting.